The Spanish and the Russian Quevedo: Difficulties in translating a conceptist sonnet - M. B. Smirnova (Шаги)
Although Francisco de Quevedo’s sonnets, unlike, for example, Shakespeare’s, have not become a fact of Russian culture and literature, the existing experience of translating them is of interest from the point of view of the very possibility of conveying to the modern reader the meaning and pragmatics of the Baroque text. The peculiarities of the Spanish author’s poetic language are associated with the specifics of lyrical subjectivity, which is far from romantic and post-romantic ideas about authorship as a confession based upon personal experience, but is a set of masks or roles that he constructed in accordance with one or another poetic canon. One of these canonical languages was Petrarchism, which largely determined the language of Quevedo’s love sonnets. The novelty of the Spanish Baroque author lies in the fact that, relying on Petrarchist conventions, he subjects them to witty reflection and turns them into the subject of a conceptual game. At the same time, the reflective nature of the sonnet as a Renaissance genre is reduced to the poetic word. The true hero of Quevedo’s sonnets is not himself or even the feeling of love as such, but a conceit (concepto), the pragmatic goal of this kind of poetry is to surprise the reader and involve him in an intellectual adventure. Analysis of two sonnets and their Russian versions (by A. Koss and A. Geleskul) allows us to draw conclusions about different translation strategies (literal and adapting), which nevertheless lead in different ways to the weakening and erosion of the conceit. The advantage of the first translation is its philological precision. The second impresses with its poetical qualities and naturalness. However, in the first case, the endeavor to follow the original step by step leads to overly heavy syntactic and grammatical constructions. This distracts the reader, preventing him from following the sophisticated paradigm of metaphors into which the basic conceit unfolds. In the second case, the intellectual and rhetorical basis of the sonnet, the supporting elements of the final conceit are sacrificed.